Innovation in Learning Indonesian Language and Literature in the Digital Era: A Technological and Skills-Based Approach - Puji Lestiyani, Atika; Salpa Riansi, Erwin (International Proceedings of Nusantara Raya, 2024)
Indonesian language learning in the digital era requires relevant innovations to answer the challenges of the 21st century. This study aims to integrate technology and skill-based approaches in Indonesian language learning to improve language skills. This research uses the literature study method. The findings show that the integration of technology such as social media, digital learning apps and online platforms helps to improve students' motivation, creativity and communication skills. However, challenges such as limited access to technology, ethical use, and teacher competence are still the main obstacles. This research recommends strengthening technology infrastructure, teacher training and education policies that support digital transformation. Innovation in Indonesian language learning is essential to improve the quality of education and students' language skills. Innovation in Indonesian language learning has a significant positive impact on the teaching-learning process. With more creative and interactive approaches, such as the use of digital technology, students become more motivated to learn. Penerapan inovasi dalam pembelajaran, terutama melalui teknologi, memiliki dampak positif dan negatif yang signifikan. Secara positif, teknologi meningkatkan efisiensi waktu dan biaya dengan mengurangi kebutuhan akan materi cetak dan ruang kelas secara fisik, sehingga proses belajar-mengajar dapat dilakukan dari mana saja, namun infrastruktur teknologi yang belum merata di seluruh Indonesia menjadi salah satu kendala utama. Selain itu, kompetensi guru dalam menggunakan teknologi dan memanfaatkan media digital dalam pembelajaran masih terbatas. Penelitian ini bertujuan untuk mengeksplorasi manfaat, tantangan, dan dampak dari inovasi pembelajaran bahasa Indonesia melalui integrasi teknologi dan pendekatan berbasis keterampilan. Penelitian ini juga diharapkan dapat memberikan wawasan yang komprehensif tentang bagaimana teknologi dapat digunakan untuk meningkatkan kemampuan berbahasa siswa sekaligus menjawab tantangan pendidikan di era digital.